2016
DOI: 10.1161/atvbaha.115.307397
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular ATP Induces Vascular Inflammation and Atherosclerosis via Purinergic Receptor Y 2 in Mice

Abstract: Objective— A solid body of evidence supports a role of extracellular ATP and its P2 receptors in innate and adaptive immunity. It promotes inflammation as a danger signal in various chronic inflammatory diseases. Thus, we hypothesize contribution of extracellular ATP and its receptor P2Y 2 in vascular inflammation and atherosclerosis. Approach and Results— Extracellular ATP induced l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(46 citation statements)
references
References 47 publications
0
44
1
1
Order By: Relevance
“…ATP treatment did not change the increase of infiltrated peritoneal Gr-1/Mac-1-positive cells (Figure 3C). This result contrast with previous publications showing that ATP increases granulocyte infiltration to the peritoneum (20, 21); however, in such studies, ATP was used at lower concentration and without endotoxin that might explain the differences.…”
Section: Resultscontrasting
confidence: 99%
“…ATP treatment did not change the increase of infiltrated peritoneal Gr-1/Mac-1-positive cells (Figure 3C). This result contrast with previous publications showing that ATP increases granulocyte infiltration to the peritoneum (20, 21); however, in such studies, ATP was used at lower concentration and without endotoxin that might explain the differences.…”
Section: Resultscontrasting
confidence: 99%
“… 7–10 Moreover recent studies have shown that administration of extracellular ATP to ApoE − / − mice exacerbated atherosclerosis by increasing leukocyte adhesion and migration. 9 Furthermore, inflammatory stimuli such as LPS 42 , TNF, 35 hypoxia, 36 and high glucose/palmitate 10 all increase extracellular ATP release from endothelial cells, further supporting a role of extracellular ATP in endothelial inflammatory responses. Thus we suggest that mechanical shear-dependent upregulation of P2X7 at atheroprone sites may be important in the initiation of atherosclerosis by transducing extracellular ATP into pro-inflammatory signalling responses.…”
Section: Discussionmentioning
confidence: 94%
“…Given that more internal energy failed to produce more surviving RGCs, we questioned whether supplying extrinsic ATP would confer any benefit for RGC survival. ATP was injected at a relatively high dose (50 mg/kg) [37,38] and a low dose (5 lmol/kg; *2.865 mg/kg) [39]. Intraperitoneal injections did not have a significant effect on RGC survival in either injured or intact eyes (Fig.…”
Section: Neither Systemic Increases In Internal Energy Levels Nor Supmentioning
confidence: 96%